Electrocatalytic activities of platinum and palladium catalysts for enhancement of direct formic acid fuel cells: An updated progress - Che Ramli Z.A.; Pasupuleti J.; Tengku Saharuddin T.S.; Yusoff Y.N.; Isahak W.N.R.W.; Baharudin L.; Tak Yaw C.; Koh S.P.; Tiong Kiong S. (Elsevier B.V., 2024)
Direct formic acid fuel cells (DFAFCs) have become an important technology and a clean energy source for various applications. However, some drawbacks in DFAFC applications, such as sluggish kinetics of formic acid oxidation (FAO) reaction at the anodic side, significantly affect DFAFC performance. An excellent catalyst, platinum (Pt), is very effective and performs excellently in FAO, but it is expensive and tends to form carbon monoxide-poisoning species on the catalyst surface. Therefore, new strategies must be developed to overcome problems related to Pt and simultaneously reduce or replace the use of Pt catalysts. This review paper covers the electrocatalytic activities of platinum and palladium (Pd)-based catalysts, which are commercial catalysts and effective for FAO and DFAFC applications. In this paper, the current progress of electrocatalyst development for anodic FAO and DFAFC applications using commercial Pt and Pd catalysts is presented, focusing on the understanding of Pt and Pd catalytic activities with the addition of alloys, metallic metals, trimetallic/tetrametallic metals, transition metals, and metal oxides. Highly potential nanostructured carbon catalyst supports (graphene-based materials, carbon nanotubes, carbon nanofibers, and graphitic carbon nitride) for FAO and DFAFC applications are also discussed. This review article also examines the literature related to Pt and Pd electrocatalysts on the synthesis routes, electrochemical conditions, and fuel cell performance within 10 years from 2013 until 2023. The challenges and strategies for electrocatalyst commercialization in the field are discussed at the end of the paper. 2023 THE AUTHORS